Estimation of Direct Solar Radiation on High Mountain Region, Jomson, Nepal - Shrestha, Prakash M.; Gupta, Suresh Pd.; Joshi, Usha; Chapagain, Narayan P.; Karki, Indra B.; Poudyal, Khem N. (Patan Prospective Journal, 2022)
The main aim of the study is to estimate direct solar radiation over high mountain region of Jomsom (Nepal) (28.47 °N, 83.83 °E, 2,700 m above sea level) for a period of year 2012. Aerosol optical depth (AOD) and total ozone column data are derived from NASA website. Daily atmospheric transmittance due to different parameters for direct solar radiation is calculated. The effect of different parameters on the direct solar radiation was analyzed. The maximum and minimum monthly average of direct solar radiation values were found 1208 ± 22 W/m2 in January and 1021 ± 46 W/m2 in June respectively. Annual average of direct solar radiation is 1106 ± 70 W/m2. Result of this research work is beneficial for the further identification, impact and analysis of direct solar radiation at different places, agriculture, energy harvesting.